GW24-e2374 Deficiency in Fractalkine Receptor Reduces Post-infarction Cardiac Rupture. (1st October 2013) - Liang, Su; Wanling, Xuan; Liang, Shen; Xixian, Li; Wenyan, Lai; Dingli, Xu; Yulin, Liao
Abstract : Objectives: Our previous studies have demonstrated that fractalkine (FKN) promotes myocardial inflammation and fibrosis which are known to might play a crucial role in post-infarction cardiac rupture. However, it is completely unknown whether FKN has any influence on cardiac rupture. Here we attempted to investigate the hypothesis that fractalkine predisposes cardiac rupture. Methods: Mice were subjected to the left coronary artery ligation to induce myocardial infarction. The tissues were collected for RNA or protein level detection. TTC staining was performed for infarct size determination. Immunohistochemistry was used for the localisation of αE-catenin in myocardium. Statistical differences were evaluated by one-way analysis of variance. The overall survival of MI mice was evaluated using Kaplan-Meier survival analysis. Results: In a murine myocardial infarction model, FKN protein levels were significantly higher than in sham group. We found that the incidence of post-MI cardiac rupture reduced in CX3CR1-/- (FKN receptor) mice (42% in wild type vs. 19% in knockout mice, p < 0.05). Furthermore, the infarct size of CX3CR1-/- mice was much smaller than that of wild type littermates. The expression of ICAM-1, MMP-9 (by PCR) and MPO (by Immunohistochemistry) increased in wild type mice after myocardial infarction, which was inhibited in CX3CR1-/- mice. Importantly, the expression of αE-catenin significantly decreased in wild type C57 mice after myocardial infarction, while it was only slightly reduced in CX3CR1-/- mice. Conclusions: Fractalkine predisposes cardiac rupture by promoting myocardial inflammation and down-regulating αE-catenin.